Development of a polyphagous leaf beetle on different host plant species and its detoxification of glucosinolates - Friedrichs, Jeanne; Schweiger, Rabea; Geisler, Svenja; Neumann, Judith M.; Sadzik, Sullivan J. M.; Niehaus, Karsten; Müller, Caroline (Frontiers in Ecology and Evolution, 2022)
Herbivores face a broad range of defences when feeding on plants. By mixing diets, polyphagous herbivores are assumed to benefit during their development by gaining a better nutritional balance and reducing the intake of toxic compounds from individual plant species. Nevertheless, they also show strategies to metabolically cope with plant defences. In this study, we investigated the development of the polyphagous tansy leaf beetle, Galeruca tanaceti (Coleoptera: Chrysomelidae), on mono diets consisting of one species [cabbage (Brassica rapa), Brassicaceae; lettuce (Lactuca sativa) or tansy (Tanacetum vulgare), Asteraceae] versus two mixed diets, both containing tansy. Leaves of the three species were analysed for water content, carbon-nitrogen-ratio (C/N), specific leaf area and trichome density. Furthermore, we studied the insect metabolism of two glucosinolates, characteristic defences of Brassicaceae. Individuals reared on cabbage mono diet developed fastest and showed the highest survival, while the opposite was the case for individuals kept on tansy mono diet. Cabbage had the lowest water content and C/N ratio, while tansy had the highest water content, C/N ratio and trichome density. Lettuce showed the highest specific leaf area and had no trichomes. Analysis of insect samples with UHPLC-QTOF-MS/MS revealed that benzyl glucosinolate was metabolised to N-benzoylglycine, N-benzoylalanine and N-benzoylserine, while 4-hydroxybenzyl glucosinolate was metabolised to N-(4-hydroxybenzoyl)glycine. MALDI-Orbitrap-mass spectrometry imaging indicated the localisation of these metabolites in the hindgut region. Our results highlight that G. tanaceti deals with toxic hydrolysis products of glucosinolates by conjugation with different amino acids, which may enable this species to develop well on cabbage. The high trichome density and/ or specific plant chemistry of tansy may lower the digestibility of its leaves, leading to a poorer beetle development on pure tansy diet or diet mixes containing tansy. Thus, diet mixing is not necessarily beneficial, if one of the plant species is strongly defended.